Perkembangan Hukum Perpajakan di Indonesia - Sartono Sartono (Journal on Education, 2023)
Tax is one of the most important instruments in determining a country's income. Considering that the role of taxes is very important for a country, the government requires that everyone is subject to taxes, so that there are regulations that have been set by the government regarding taxes. Taxpayers are also said to fulfill their tax obligations if they have fulfilled material and formal tax law. At a practical level, formal provisions on taxation can be realized through the KUP Law. Currently the Indonesian government is still discussing the KUP Law which is expected to be able to encourage increased taxpayer compliance while at the same time increasing revenue without leaving the aspect of justice. The research method is observation and study of literature, the use of books and educational theory, legal theory and try to compare educational study materials with legal research study materials. Based on the discussion that has been put forward, the author can conclude that tax law is a rule governing tax collection in which the people are the taxpayers and the state/government is the tax collector, where the tax money collected will later be returned to the community/people in the form of welfare. . public (shared) by the government.